Financial Distress Assessment Through Altman Z-Score - Farid Maulana (Journal of Economics and Business UBS, 2024)
This research aims to assess the financial distress condition of PT Waskita Karya Tbk (WSKT), a state-owned construction company in Indonesia, from 2017 to 2022 using the Altman Z-Score model. The Altman Z-Score combines financial ratios to predict the likelihood of bankruptcy. Secondary data derived from WSKT’s financial statements were analyzed quantitatively using the Z-Score formula for non-manufacturing firms. The findings indicate that WSKT has experienced significant financial distress. In 2017 and 2022, WSKT was in the Distress Zone with scores of 0.96570 and 0.78271 respectively. The company was also in distress in 2020 with a negative score of -1.12303. For 2018, 2019 and 2021, WSKT was in the Grey Zone with scores of 1.51502, 1.05679 and 1.17451. WSKT did not achieve Safe Zone status during the six years examined. Overall, 66.67% of the period reviewed falls in the Distress Zone, predicting a high bankruptcy risk for WSKT. To address this financial vulnerability, recommendations include conducting operational optimization to enhance efficiency and profitability, diversifying business portfolios to tap into promising segments, and proactively monitoring financial health using analytical models like Altman Z-Score. With disciplined implementation of strategies to rectify distressed ratios, WSKT can achieve financial stability.